RECQL4 helicase has oncogenic potential in sporadic breast cancers - Arora, Arvind; Agarwal, Devika; Abdel-Fatah, Tarek M.A.; Lu, Huiming; Croteau, Deborah L.; Moseley, Paul; Aleskandarany, Mohammed A.; Green, Andrew R.; Ball, Graham; Rakha, Emad A.; Chan, Stephen Y.T.; Ellis, Ian O.; et al. (Wiley, 2016)
RECQL4 helicase is a molecular motor that unwinds DNA, a process essential during DNA replication and DNA repair. Germ-line mutations in RECQL4 cause type II Rothmund–Thomson syndrome (RTS), characterized by a premature ageing phenotype and cancer predisposition. RECQL4 is widely considered to be a tumour suppressor, although its role in human breast cancer is largely unknown. As the RECQL4 gene is localized to chromosome 8q24, a site frequently amplified in sporadic breast cancers, we hypothesized that it may play an oncogenic role in breast tumourigenesis. To address this, we analysed large cohorts for gene copy number changes (n = 1977), mRNA expression (n = 1977) and protein level (n = 1902). Breast cancer incidence was also explored in 58 patients with type II RTS. DNA replication dynamics and chemosensitivity was evaluated in RECQL4-depleted breast cancer cells in vitro. Amplification or gain in gene copy number (30.6%), high-level mRNA expression (51%) and high levels of protein (23%) significantly associated with aggressive tumour behaviour, including lymph node positivity, larger tumour size, HER2 overexpression, ER-negativity, triple-negative phenotypes and poor survival. RECQL4 depletion impaired the DNA replication rate and increased chemosensitivity in cultured breast cancer cells. Thus, although recognized as a ’safe guardian of the genome’, our data provide compelling evidence that RECQL4 is tumour promoting in established breast cancers.